Drinking Natural Mineral Water Maintains Bone Health in Young Rats With Metabolic Acidosis - Tan, Yao; Xu, Anwei; Qiu, Zhiqun; Wang, Lingqiao; Wang, Jia; Luo, Jiaohua; Zeng, Hui; Jin, Huidong; Wang, Yushu; Xue, Jing; Huang, Yujing; Shu, Weiqun (Frontiers in Nutrition, 2022)
Introduction Metabolic acidosis affects bone health. It remains unclear whether drinking natural mineral water is better for maintaining bone health in the youth with metabolic acidosis. Materials and methods Sixty young female rats (three-weeks-old) were randomly divided into three groups and drank purified water (PW, as control), bicarbonate-rich natural mineral water (Bic-NMW), or sulfate-rich natural mineral water (Sul-NMW), which respectively contained calcium (0.17, 155, and 175mg/L), bicarbonate (0, 1360, and 139 mg/L) and sulfate (0, 35.6, and 532 mg/L), for 16 weeks. In the last three weeks, metabolic acidosis was induced in ten rats per group by adding NH4Cl (0.28 mM) to drinking water. The rats’ blood, urine, and femur were collected for assessing acid-base status, calcium metabolism, bone microstructure, and strength. The difference between the three groups was determined using one-way ANOVA followed by the Student-Newman-Keuls test or Dunnett’s T3 test. Results Compared with the PW rats, the Bic-NMW rats and the Sul-NMW rats had less urine net acid excretion (-1.51, 0.20 VS. 10.77, EQ/L), higher bone mineral density (442.50, 407.49 VS. 373.28, mg/mm3), growth cartilage width (271.83, 283.83 VS. 233.27, μm) and cortical trabecular area (9.33, 9.55 VS. 5.05, mm2), and smaller cortical marrow cavity area (5.40, 5.49 VS. 7.27, mm2) in the femur (P<0.05). Besides, the Bic-NMW rats had less serum calcium (2.53 VS. 2.68, mmol/L) and C-terminal cross-linked telopeptide of type-I collagen (1.35 VS. 1.93, ng/mL), and higher serum calcitonin (0.61VS. 0.39, μg/L), femoral trabecular thickness (0.10 VS. 0.09, μm), bone volume/total volume (0.42 VS. 0.34, %), cortical bone area (15.91 VS. 12.80, mm2) and ultimate stress (35.12 VS. 29.32, MPa) (P<0.05). The Sul-NMW rats had more osteoclasts (22.50 VS. 11.54, cells/field) (P<0.05). Conclusions Drinking natural mineral water, especially bicarbonate-rich natural mineral water, is effective in improving bone health in young rats with metabolic acidosis. These benefits include maintaining bone mineral density, and improving bone microstructure and biomechanical properties via moderating metabolic acidosis.